Decision-Making approach for evaluating suitable hybrid renewable energy system for SMEs in Ghana. Issue 1 (31st December 2022) - Odoi-Yorke, Flavio; Abofra, Nicholas; Kemausuor, Francis
Abstract : In this study, decision-making approaches have been utilised to identify the best hybrid renewable energy system suitable for Small and Medium-Sized Enterprises (SMEs) operating in Ghana. The study considered seven different hybrid energy systems, including, PV/battery (Option A), diesel/battery (Option B), PV/diesel (Option C), PV/battery/diesel (Option D), PV/diesel/grid (Option E), PV/battery/grid (Option F) and diesel/grid (Option G) under 25 different criteria for assessment. Six notable decision-making methods were employed to rank and check the resilience of the options. The ultimate options rankings are as follows: Case 1 (D > E>G > C>B > F>A), Case 2 (D > E>G > C>B > F>A), and Case 3 (D > E>C > G>B > F>A). Option D came out top, followed by Option E. The results indicate that an inclusive investment in PV/battery/diesel and PV/diesel/grid systems has a good prospect of achieving sustainable energy for businesses in Ghana. The findings are important to stakeholders, policymakers, and investors in the renewable energy sector towards developing green businesses in Ghana.